Ordering, naming, numbering: how a Crown’s history and memory are organised (History Journal «Jerónimo Zurita», 2024)
The union of the kingdom of Aragon with the county of Barcelona immediately caused both political and historical reflection on the traditions that were going to merge. With time and the repetition of the same names for some monarchs, the need to distinguish one from the another emerged when the names were out of a genealogical chain. The different forms are analyzed here, expressing the level of kinship, through a nickname or the use of numerals. In this regard, it is argued which is the historically correct way to use them when speaking of the Crown of Aragon.
Keywords: Crown of Aragon; Kings; Historiography; Organizing the Past; House of Aragon